"Friendly to all beings": Annie Besant as ethicist. Issue 2 (4th March 2021) - Leland, Kurt
ABSTRACT: Annie Besant (1847–1933) has rarely been identified as a philosopher. Her work as an ethicist has been obscured by the reaction of critics to her abandonment of Anglican Christianity for serial engagements with theism, atheism, collectivist socialism, and Theosophy – often characterized as fickle and indecisive 'conversions'. However, Besant saw these engagements as stages in a quest for a universally applicable system of morality and conduct founded on empirical principles, and as valid as any scientific law. This article positions Besant as an ethicist working in the virtue ethics tradition, as defined by Rosalind Hursthouse, first by examining Besant's ethical evolution, driven by the philosophical problem of whether ethics can exist without metaphysics (which she sometimes phrased as 'Can morals exist without religion?'), and second, by identifying an anonymously published Advanced Text Book of Hindu Religion and Ethics (1903) as the most complete expression of her syncretic ethical system.